Analisis Kecenderungan Musiman Tinggi Gelombang Signifikan di Laut Indonesia Tahun 1980-2020 Untuk Mendukung Pembangunan Pesisir Berkelanjutan - Fahmi, Muhammad Baharudin; Wirayuhanto, Harish; Dwito Armono, Haryo; Zikra, Muhammad; Lorentius, Suratno (Universitas Trunojoyo Madura, 2025)
Sea level rise, as one of the consequences of global climate change, has significantly impacted oceanographic dynamics, particularly wave characteristics. One of the most critical affected parameters is significant wave height, which directly influences maritime safety, the sustainability of fisheries, the stability of coastal infrastructure, and the risk of coastal erosion and tidal flooding. As an archipelagic nation with the second-longest coastline in the world, Indonesia is highly vulnerable to such changes. Therefore, understanding the spatial and temporal trends in significant wave height is essential to support effective adaptation and mitigation policies in coastal regions. This study aims to analyze the trend of increasing significant wave height in Indonesian waters using ERA5 reanalysis data from the European Centre for Medium-Range Weather Forecasts (ECMWF) over the period from 1980 to 2020. The trend analysis was conducted using non-parametric statistical methods, namely the Mann-Kendall test to detect statistically significant trends and Sen’s Slope Estimator to quantify the rate of change. A significance level of 0.05 was applied in the analysis. The results indicate a significant upward trend in significant wave height across several Indonesian maritime regions. Conversely, the northern waters of Central Java and the northern region of Masalembu Island exhibited no statistically significant trend across seasons. The Banda Sea and southern Papua experienced significant increases during the dry season (JJA) and the second transitional season (SON), with a peak rate of 1.70 cm/year. In the southern waters of Lombok Island, positive trends were observed in the wet season (DJF) and the first transitional season (MAM), with rates reaching 1.46 cm/year. The highest trend was recorded in the southern waters of Java during the wet season (DJF), at 1.72 cm/year. These findings suggest that most Indonesian waters are experiencing significant changes in wave characteristics as a result of climate change, highlighting the urgency for long-term oceanographic monitoring and the integration of wave data into coastal development and climate adaptation strategies.